Why can't I exercise during pregnancy? Time to revisit medical 'absolute' and 'relative' contraindications: systematic review of evidence of harm and a call to action. Issue 23 (8th June 2020) - Meah, Victoria L; Davies, Gregory A; Davenport, Margie H
Abstract : Background: Clinical guidelines recommend pregnant women without contraindication engage in regular physical activity. This is based on extensive evidence demonstrating the safety and benefits of prenatal exercise. However, certain medical conditions or contraindications warrant a reduction, modification or cessation of activity due to potential health risks. Aim: To review and evaluate the evidence related to medical disorders which may warrant contraindication to prenatal exercise. Methods: Online databases were searched up to 5 April 2019. Forty-four unique studies that reported data on our Population (pregnant women with contraindication to exercise), Intervention (subjective/objective measures of acute or chronic exercise), Comparator (not essential) and Outcomes (adverse maternal or fetal outcomes) were included in the review. Key findings: We found that the majority of medical conditions listed as contraindications were based on expert opinion; there is minimal empirical evidence to demonstrate harm of exercise and benefit of activity restriction. We identified 11 complications (eg, gestational hypertension, twin pregnancy) previously classified as contraindications where women may in fact benefit from regular prenatal physical activity with or without modifications. However, the evidence suggests that severe cardiorespiratory disease, placental abruption, vasa previa, uncontrolled type 1 diabetes, intrauterine growth restriction, active preterm labour, severe pre-eclampsia and cervical insufficiency are associated with strong potential for maternal/fetal harm and warrant classification as absolute contraindications. Conclusion: Based on empirical evidence, we provide a call to re-evaluate clinical guidelines related to medical disorders that have previously been considered contraindications to prenatal exercise. Removing barriers to physical activity during pregnancy for women with certain medical conditions may in fact be beneficial for maternal–fetal health outcomes.